2022
DOI: 10.48550/arxiv.2201.02158
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Introducing Randomized High Order Fuzzy Cognitive Maps as Reservoir Computing Models: A Case Study in Solar Energy and Load Forecasting

Abstract: Fuzzy Cognitive Maps (FCMs) have emerged as an interpretable signed weighted digraph method consisting of nodes (concepts) and weights which represent the dependencies among the concepts. Although FCMs have attained considerable achievements in various time series prediction applications, designing an FCM model with time-efficient training method is still an open challenge. Thus, this paper introduces a novel univariate time series forecasting technique, which is composed of a group of randomized high order FC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…For example, Orang et al proposed a novel univariate time series forecasting technique, called randomized high order FCM models (R-HFCM). The obtained results confirm the proposed R-HFCM model is superior to the other methods [7]. Haida et al proposed a regression-based daily peak load forecasting method and a conversion technique, which reduced the large forecasting error caused by the nonlinear characteristics [8].…”
Section: Introductionsupporting
confidence: 64%
“…For example, Orang et al proposed a novel univariate time series forecasting technique, called randomized high order FCM models (R-HFCM). The obtained results confirm the proposed R-HFCM model is superior to the other methods [7]. Haida et al proposed a regression-based daily peak load forecasting method and a conversion technique, which reduced the large forecasting error caused by the nonlinear characteristics [8].…”
Section: Introductionsupporting
confidence: 64%
“…Finally, in the context of reservoir computing, Colla et al presented a novel application of the modeling of industrial processes in energy management [245]. Orang et al, in their paper, reported a time-series forecasting technique composed of a group of randomized high-order FCM models labeled R-HFCM using an RL algorithm [246].…”
Section: Modeling Of Energy Demand and Supplymentioning
confidence: 99%
“…Only a few compare them to other types of recurrent neural networks like LSTMs as well [27]. Even fewer publications consider multiple data sets or different types of data: In [33] the authors use deep ESN to predict energy consumption as well as wind power generation and in [34], high order fuzzy cognitive maps are used as reservoir computing models to predict solar energy as well as load. While there are first applications of RC for probabilistic load forecasting, like the authors show in [35] by coupling the ESN with multiple methods of uncertainty, we focus on determining point forecasts in this work.…”
Section: Introductionmentioning
confidence: 99%